Cartilage Repair and Regeneration - Zorzi, Alessandro R.; Batista de Miranda, Joao (IntechOpen, 2018)
This work is the result of a partnership that began in 2011, when I received for the first time the invitation to be the scientific editor of a book on bone grafting, by the still little publisher known as InTech. Now six years later, InTech has grown and thrived. My respect and warm approval for the quality of the publisher's work only increased. The hyaline cartilage is a tissue that challenges tissue engineering and regenerative medicine because of its avascular nature. In the 11 chapters of this book, the reader will find texts written by researchers working on advanced topics related to basic laboratory research, as well as excellent reviews on the clinical use of currently available therapies.